Stable Photoelectrochemical Hydrogen Evolution for 1000 h at 14% Efficiency in a Monolithic Vapor-fed Device. Issue 6 (19th March 2020) - Kistler, Tobias A.; Um, Min Young; Agbo, Peter
Abstract : This report builds on our recent disclosure of a fully-integrated, photoelectrochemical (PEC) device for hydrogen evolution using a structure incorporating a III–V triple-junction photovoltaic (PV) embedded in a Nafion membrane. Catalyst integration is realized by compression of catalyst-modified, carbon electrodes against the front and back PV contacts, resulting in a wireless, monolithic PEC assembly. Using this device architecture, we demonstrate significant enhancements in device stability and longevity, by transitioning from a liquid-water to water-vapor anode. Our use of a gas-fed anode enables 1000 h of cumulative device operation at a peak solar-to-hydrogen efficiency of 14%, during simulated, solar illumination at 1 sun and outdoor, diurnal cycling. Vapor-fed water oxidation is shown to reduce drops in device performance by mitigating the corrosion effects that are commonly associated with full-aqueous immersion of the electrochemical and photovoltaic elements in PEC devices.